Comparison of Outcomes of Circumcisions among Children 0-4 years by using Gomco Versus Plastibell Techniques - Syed Asif Hussain Shah, Muhammad Tauqeer Aslam, Muhammad Saad Zulfiqar, Mazhar Rafi, Muhammad Tahir Mehmood, Mushtaq Ahmed, Hafiz Babar Ghafoor (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: We aimed to compare the rate of complications of Gomco and Plastibell circumcision techniques ininfants. Study design:Prospective Randomized Clinical TrialStudy. Place and duration of study:Department of Pediatric Surgery, Sheikh Zayed Hospital, Rahim Yar Khanfor six months from August 2020 to July 2021. Patients and method: A total of 80 patients were enrolled in the study, equally divided into two groups. Group 1 included patients undergoing circumcision via the Gomco technique, while group 2 circumcised with the Plastibell method. All healthy male patients aged one day old to 4 years of age were included. Patients with any congenital abnormalities, e.g., urethral or penile shaft abnormality, local infection, hypospadias. Jaundice and bleeding disorders were excluded. All procedures weredone under local anesthesia, postoperatively topical antibiotic was prescribed to each patient. Data was entered and analyzed using SPSS 25.0. Frequencies and percentages were expressed for qualitative variables like gender and postoperative outcomes, i.e., bleeding, penile edema, and redundant skin. Mean ± S.D represented quantitative variables like age, weight, and BMI. A Chi-square test was used to compare the complication rate between both groups. A p-value ≤0.05 was considered significant. Results: In the Gomco technique, there was no Penile edema, surgical site infection, hematoma, and need for Repeat surgery/manipulation. We found that bleeding was more common in Gomco compared to Plastibell. On the other hand, penile edema, reductant skin, slipped ring, and the need for repeated surgery/manipulation was more often in the Plastibell technique. Conclusion: We propose using the Gomco method for circumcision because of its lower rate of complication and better aesthetic outcome than the Plastibell method.